Learning Mapag Layung traditional dance in improving the kinesthetic intelligence of 5–6-year-old children at RA Raudhatul Falah Tangerang - Nurhayati, Nurhayati; Rokhman, Nissa Mawarda (Humanities Horizon, 2025)
Traditional dances are believed to be a cultural heritage for the next generation because they are typical dances of a region that have been practiced since ancient times and are still preserved today. The ability to move or control the body by coordinating the hemispheres of the brain that regulate all body movements is known as kinesthetic intelligence. The body's high awareness of movement is a characteristic of children with extraordinary motor intelligence. This research was conducted at RA Raudhatul Falah which is located at Jalan Tohir No. 29 Kp. Gebang Rt 006 Rw 002 Gebang Raya Village, Periuk District, Tangerang City. The researchers found that many students still had difficulty in practicing stepping and walking straight (stepping forward, backward, right side, left side). This is based on the findings of the initial observations they made in the classroom. The researcher uses classroom action research (PTK) as the research methodology. PTK involves learning with a group of people, identifying problems, taking action to solve problems, and evaluating the success of those efforts. If the results are not satisfactory, repeat the process, if the results meet the expected criteria, the PTK is considered successful. The children's activity observation sheet is a data collection tool used in this study, which uses an observation method. The research analysis technique used is quantitative descriptive. This study used 2 cycles, from the two cycles there was a significant increase. Giving variants at each meeting supports an increase in each cycle. The criteria for developing very well increased by 28.57 percent in the first cycle. This achieved the success target of 64.29 percent with very good development criteria in the next cycle, namely the second cycle. Therefore, the cycle is stopped because it is in accordance with the desired results.